2018
DOI: 10.1177/1054773818773285
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nurse-Led Case Management in Cancer Care: Systematic Review

Abstract: Cancer survivors need accountable, patient-centered and lifelong care. Case management has been shown effective at providing quality care and at reducing both hospital access and health care costs. However, how effective case management in cancer care is to date unclear. This systematic review examines recent evidence of the effectiveness of nurse-led case management in adults with cancer. The Cochrane processes and PRISMA statements guided this systematic review. The methodological risk of bias was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 26 publications
1
41
0
2
Order By: Relevance
“…The importance of this theme for patient-centered care is also reflected in the questionnaire as the ‘coordination and integration of care’ dimension was assessed in six closed-ended questions. Recent systematic reviews have shown that cancer care coordination interventions, such as increased communication across multidisciplinary teams, patient navigation, home telehealth, self-management education and nurse case management, have the potential to improve a range of cancer related outcomes, including measures of patient experience with care, and quality of life [ 29 32 ]. It may be beneficial to further develop such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this theme for patient-centered care is also reflected in the questionnaire as the ‘coordination and integration of care’ dimension was assessed in six closed-ended questions. Recent systematic reviews have shown that cancer care coordination interventions, such as increased communication across multidisciplinary teams, patient navigation, home telehealth, self-management education and nurse case management, have the potential to improve a range of cancer related outcomes, including measures of patient experience with care, and quality of life [ 29 32 ]. It may be beneficial to further develop such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on care management in chronic health populations other than PD revealed its potential in improving patient outcomes [ 8, 9 ], quality of life [ 10 ], patient satisfaction [ 11 ], and also in preventing complications that also common occur in PD patients, including reduction in feelings of anxiety [ 12, 13 ] and depressive symptoms [ 13, 14 ]. Research has demonstrated that implementation of care management models is successful in guiding quality improvement and in providing effective and high quality of chronic care [ 8– 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a systematic review (9 experimental studies: 3 randomized controlled trials and 6 controlled before-and-after study) concluded that participants saw significant improvement in the quality of life measures with case management. [12] However, little robust evidence from randomized controlled studies was available to confirm this conclusion.…”
Section: Introductionmentioning
confidence: 99%